Peran Lembaga Pengelolaan Hutan Desa (LPHD) Desa Tuwunag Kabupaten Pulang Pisau Kalimantan Tengah dalam Perlindungan Satwa Liar - Awalul Fatiqin; Ahmad Muammar Kadafi; Yahya Febrianto; Thathit Suprayogi; Ike Apriani; Kamison; Adventus Panda (Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur, 2024)
Assistance activities for the community, especially the protection and security section of the Tuwung LPHD area, provide a strong basis for improving village forest management, by identifying problems and challenges faced before and after activities, as well as real data on regional potential including fauna inventory and existing management practices. The evaluation shows a good understanding of the area management section, which contributes to the development of superior human resources for fauna management at LPHD Tuwung. Data from the protection and security section of the Tuwung LPHD area, regarding the role of the area management section, can continue to be improved through training approaches to management and maintenance of fauna, as well as community awareness and development. Management of fauna in village forest areas needs to be carried out wisely and sustainably. Training on management and maintenance of fauna in the LPHD environment for village communities is very necessary as an effort to increase competence in maintaining the sustainability of forest ecosystems, including efforts to increase community awareness about the need to preserve fauna in village forests. The policy implications of this activity emphasize the importance of developing policies that support training and education of village communities in the management and maintenance of fauna. Such policies should include the provision of adequate resources and technical support to ensure the implementation of sustainable and effective forest management practices, as well as understanding the regulatory framework that strengthens the protection of village forest fauna and ecosystems through active community participation.